Impact of calcineurin inhibitor‐free immunosuppression on de novo donor‐specific antibody formation in liver transplant recipients. (1st March 2022) - Meszaros, Magdalena; Dubois, Valérie; Congy‐Jolivet, Nicolas; Hamada, Sarah; Thevenin, Céline; Faure, Stephanie; Boillot, Olivier; Kamar, Nassim; Pageaux, Georges‐Philippe; Del Bello, Arnaud; Dumortier, Jérôme
Abstract: Background & Aims: Low calcineurin inhibitor (CNI) levels expose liver transplant recipients to rejection episodes and potentially to antibody‐mediated rejection. There are little data on the impact of CNI‐free immunosuppression on de novo donor‐specific HLA antibody (dnDSA) development. Here we evaluated the prevalence of dnDSA in liver transplant recipients on CNI‐free maintenance regimens and their associations with histopathological abnormalities of allografts. Methods: Seven hundred and twenty‐seven liver transplant recipients underwent a first liver transplant between 2000 and 2018 in three French transplant centres and had protocolized follow‐up with dnDSA screening and allograft biopsy 1, 5 and 10 years after transplantation. Results: CNIs were withdrawn in 166 (22.8%) patients with or without conversion to mammalian target of rapamycin inhibitors and/or maintenance with mycophenolic acid. DSA were present after withdrawal in 30.1% (50/166) patients on CNI‐free immunosuppression compared with 16% (90/561) on CNI maintenance therapy ( p < 0.001). The cumulative incidence of dnDSA 10 years after transplant was 20% in the CNI group versus 28% in the CNI‐free group ( p < 0.01). dnDSAs were associated with histological graft abnormalities (significant allograft fibrosis or rejection) (HR 2.24, 95% CI 1.2–4.1; p = 0.01). In univariate Cox regression analysis, being on a CNI‐free regimen did not impact graft histology. Conclusions: Patients on a CNI‐free IS regimen have a higher prevalence of dnDSA than patients on a standard IS regimen. dnDSAs but not CNI‐free immunosuppression were associated with abnormal allograft histology.